A study to compare the efficacy of bupivacaine versus lidocaine in the control of post dental extraction pain - Francisco, Rochelle G.; Cordero, Jose Dax Adrian B.
A study was undertaken to compare the duration of action of bupivacaine and lidocaine, and to evaluate their effectivity in controlling postoperative pain. Thirty patients were divided into two groups of fifteen. These patients were to undergo simple dental extractions of not more than three teeth on one side of the mandible. < The technique of administration employed was an inferior alveolar nerve block with a separate long buccal nerve block on the operative side of the mandible. The first group was injected with 1.8 ml. of 2% lidocaine with 1:100,000 parts of epinephrine. The participants in the second group were anesthetized with the use of a 1.8 ml. solution of .5% bupivacaine with 1:200,000 parts of epinephrine. All the patients were made to fill out pain analogue sheets that would require them to evaluate the pain they felt (or the lack of it) after the extractions. These sheets were to be filled out repeatedly every two hours until eight hours after surgery. As a result it was found that the analgesic properties of bupivacaine were retained in a considerably longer time than those of lidocaine, long after the surgical procedure had been completed.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Anesthesia in dentistry; Bupivacaine (Marcaine).; Lidocaine